Brief answers to the big questions [compact disc, unabridged] - Hawking, Stephen, 1942-2018 (Random House Audio, 2018)
Stephen Hawking was one of the greatest minds of our time and a figure of inspiration after defying his ALS diagnosis at age twenty-one. He is known for both his breakthroughs in theoretical physics as well as his ability to make complex concepts accessible for all, and was beloved for his mischievous sense of humor. Within these pages, he provides his personal views on our biggest challenges as a human race, and where we, as a planet, are heading next. Each section is introduced by a leading thinker offering his or her own insight into Professor Hawking's contribution to our understanding. The book also features a foreword by actor Eddie Redmayne, and an afterword by Hawking's daughter, Lucy Hawking.